The Clerkship Pediatric Rotation: Does Setting Matter? - Bollegala, Natasha; Garfield, Hartley; Scott, Ian; Wright, Bruce; Brenneis, Fraser; Atenafu, Eshetu; Feldman, Mark E. (Canadian Medical Education Journal, 2010)
<!–StartFragment–> ABSTRACT Background: Medical student rotations in community practice settings are increasingly common within pediatric clerkship curricula yet little evidence exists to support the quality of the educational exposure. Purpose: To assess the impact of clerkship site (community setting vs. exposure to an Academic Health Sciences Center) on the following educational outcomes: 1. Clinical Performance; 2. Examination Performance; 3. Written Assignment Performance; and 4. Successful Matching to a Canadian Pediatric Residency Program. Methods: 340 medical students from the graduating classes of 2007 and 2008 at the University of Toronto, Canada were studied. Rotation performance (clinical assessment, examination mark, and written assignment mark) and acceptance into a Canadian pediatric residency program were assessed in relation to clerkship rotation site. These outcomes were assessed while controlling for the following potential confounders: 1) Pre-clerkship career preference and 2) Pre-rotation site preference as expressed by each medical student. Results: 172 medical students completed rotations that included exposure to an academic health sciences center, while 168 medical students had exclusive exposure to the community setting. Students who completed exclusively community-based pediatric rotations received slightly higher clinical evaluations (p=0.006), but not exam marks (p=0.812) nor written assignment marks (p=0.086). Students who had expressed an interest in paediatrics as a career prior to beginning their clerkship performed better during paediatric clerkship regardless of site (p= .0003) and were more likely to choose a clerkship setting that included exposure to an Academic Health Sciences Center (p=.052). Clerkship setting was not found to impact on successful matching to a Canadian pediatric residency program (p=0.171). Discussion: These results help support the decision of curriculum committees to incorporate the use of community practice settings and inform students and faculty as to the validity of distributed medical education within the field of pediatric medical education. <!–EndFragment–>